2012
DOI: 10.1002/bmc.2779
|View full text |Cite
|
Sign up to set email alerts
|

Determination of toosendanin in rat plasma by ultra‐performance liquid chromatography–electrospray ionization–mass spectrometry and its application in a pharmacokinetic study

Abstract: Toosendanin (TSN) is a major triterpenoid existing in Melia toosendan, which has been used as a digestive tract parasiticide and insecticide but with serious hepatotoxicity. An ultra-performance liquid chromatography-electrospray ionization-mass spectrometry method was developed for determination of TSN in rat plasma. Plasma samples were separated on Acquity UPLC(TM) BEH C(18) column with acetonitrile and water as flow phase by gradient elution and determined by quadrupole mass spectrometer in negative selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…And good accuracies of 99.8, 102.2, and 99.2% were also achieved at all three concentrations been examined. The remaining amount of toosendanin at different reaction times was quantified, and the results indicated that toosendanin could be rapidly metabolized within 30 min, and hardly detected at 120 min (Figure S2), which was consistent with the pharmacokinetic results in rat [10].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…And good accuracies of 99.8, 102.2, and 99.2% were also achieved at all three concentrations been examined. The remaining amount of toosendanin at different reaction times was quantified, and the results indicated that toosendanin could be rapidly metabolized within 30 min, and hardly detected at 120 min (Figure S2), which was consistent with the pharmacokinetic results in rat [10].…”
Section: Resultssupporting
confidence: 80%
“…Previously, two LC-MS analytical methods were reported to quantify toosendanin in medicinal herbs [12] and in rat plasma [10], respectively. However, due to its limitation of using single stage MS ion, [M+Na] + or [M−H] − , for quantification, the sensitivity and dynamic linear range were unsatisfactory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been frequently reported to induce severe liver injury during clinical practice and empirical research in recent years (Yang et al, 2019; Yuen et al, 2010; J. Zheng et al, 2015), and liver cell necrosis was proven to be the main liver toxicity mechanism of CLZ (J. Zheng et al, 2015; Jie Zheng, Yu, Chen, Lu, & Fan, 2018). Toosendanin (TSN) has been identified as the main active component in CLZ and is also the main toxic compound that induces liver injury (Eng Shi & Choon Nam, 2010; X. Wang, Wang, & Wang, 2013; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional Chinese medicine, TSN has unique bioactivities and great therapeutic value, as in the inhibition of hepatitis C virus infection and suppression of the proliferation of various human cancer cell lines (Wang, Wang, & Wang, 2013). However, owing to a furan ring in its chemical structure, TSN can cause significant hepatotoxicity (Lu et al, 2016;Stepan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%